Antibiotics for the secondary prevention of coronary heart disease. (2nd October 2022) - Mansoor, Mohamed; Hamer, Oliver; Walker, Emily; Hill, James
Abstract : An estimated 200 million people live with coronary heart disease, which remains one of the leading causes of mortality and morbidity worldwide. Those living with coronary heart disease are at an increased risk of cardiovascular events, such as stroke, myocardial infarction and cardiovascular death. The pathophysiology of coronary heart disease revolves around inflammation, which leads to plaque build up. Antibiotics are known to hold anti-inflammatory and anti-oxidative properties. It has been theorised that reductions in inflammation could prevent cardiovascular events, which may reduce symptoms, risk of death and hospital admission rates in patients with coronary heart disease. This article critically appraises a systematic review that assessed the risks associated with using antibiotics as secondary prevention for coronary heart disease.